Fraudulent business practices in early Islam as reported in a classical text / Ahmad Che Yaacob and Normah Omar - Che Yaacob, Ahmad; Omar, Normah (Faculty of Accountancy, Accounting Research Institute & UiTM Press, 2014)
The main purpose of this paper is to elucidate some fraudulent business practices in early Islam. The reference material is an edited manuscript entitled Kitab al-Nazar wa al-Ahkam fi Jami Ahwal al-Suq (Book on supervision and legal decision on matters related to the market). The book, which deals with the subject of market supervision, is considered the earliest of its kind. The book was a compilation of legal opinions of a Maliki scholar Yahya ibn Umar (d. 289H/901CE), who was asked about various matters relating to business practices during his time. The fact that these legal opinions are made based on understanding of Islamic law it should be differentiated from ordinary works offiqh. In fact the book deals with real situation in the business during that times and describes actions taken by the officer in charge.